1997
DOI: 10.1002/(sici)1099-0992(199701)27:1<75::aid-ejsp809>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Maladjustment implications of self and group gender–role discrepancies: An ordered-discrepancy model

Abstract: Deviation from personal ideals and group standards has maladaptive consequences. Using insights from self-categorization and social identity theories, an ordereddiscrepancy model of maladjustment was proposed in which simultaneously deviating from both types of standards is associated with increased maladjustment for members of high status groups, except when such dual discrepancies imply that one is closer to one's ideals than is one's group. In the latter case, decreased maladjustment can be expected. For me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…Secondly, the present results do not necessarily suggest that gender-related identity is unimportant to men; indeed, there is evidence that men's psychological well-being, to a greater extent than women's, is tied to group-based notions of appropriate behaviour (e.g. Burris, Branscombe, & Klar, 1997;O'Neil, Good, & Holmes, 1995). In this context, it is interesting to note that men who identi ed themselves as non-traditional tended to report not only weaker ties to the group, but less positive group-derived feelings, than traditional men; this suggests that 'being a man' is a less desirable identity for the former subgroup.…”
Section: The Social Id Entity Of Mencontrasting
confidence: 57%
“…Secondly, the present results do not necessarily suggest that gender-related identity is unimportant to men; indeed, there is evidence that men's psychological well-being, to a greater extent than women's, is tied to group-based notions of appropriate behaviour (e.g. Burris, Branscombe, & Klar, 1997;O'Neil, Good, & Holmes, 1995). In this context, it is interesting to note that men who identi ed themselves as non-traditional tended to report not only weaker ties to the group, but less positive group-derived feelings, than traditional men; this suggests that 'being a man' is a less desirable identity for the former subgroup.…”
Section: The Social Id Entity Of Mencontrasting
confidence: 57%
“…The finding also might be explained by two important factors. First, there is pressure, particularly on African American men, to conform to groups (Staples, 1978), and individuals generally seek to be perceived as a part of a group (Burris et al, 1997;Crandell et al, 2000). Second, in the North Carolina group, where African Americans composed the majority within groups, there may have been an emphasis on group membership that primed a collective identity and made social identity more salient (Brickson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Hogg and Hains (1996) found that when groups perceive their own status to be high, there is a greater likelihood that group members will identify with the group. In fact, if attitudes differ from those held by valued social group members, individuals may experience negative emotional consequences such as lower self-esteem (Burris, Branscombe, & Klar, 1997;Pool, Wood, & Leck, 1998). Ashmore et al (2004) noted social embeddedness, or the extent to which people are reminded of their collective identity, as another important factor in making collective identity salient.…”
Section: Social Contextmentioning
confidence: 99%